Assessing hospital efficiency : non-parametric evidence for Portugal - Afonso, António (2010)
We compute DEA efficiency scores and Malmquist indexes for a panel data set comprising 68 Portuguese public hospitals belonging to the National Health System (NHS) in the period 2000-2005, when several units started being run in an entrepreneurial framework. With data on hospital services' and resource quantities we construct an output distance function, we assess by how much can output quantities be proportionally expanded without changing input quantities Our results show that, on average, the NHS hospital sector revealed positive but small productivity growth between 2000 and 2004. The mean TFP indices vary between 0.917 and 1.109, implying some differences in the Malmquist indices across specifications. Furthermore, there are significant fluctuations among NHS hospitals in terms of individual efficiency scores from one year to the other.